Polymer scaffolds facilitate spinal cord injury repair. (1st April 2019) - Zhang, Qingzheng; Shi, Bo; Ding, Jianxun; Yan, Lesan; Thawani, Jayesh P.; Fu, Changfeng; Chen, Xuesi
Graphical abstract: Abstract: During the past decades, improving patient neurological recovery following spinal cord injury (SCI) has remained a challenge. An effective treatment for SCI would not only reduce fractured elements and isolate developing local glial scars to promote axonal regeneration but also ameliorate secondary effects, including inflammation, apoptosis, and necrosis. Three-dimensional (3D) scaffolds provide a platform in which these mechanisms can be addressed in a controlled manner. Polymer scaffolds with favorable biocompatibility and appropriate mechanical properties have been engineered to minimize cicatrization, customize drug release, and ensure an unobstructed space to promote cell growth and differentiation. These properties make polymer scaffolds an important potential therapeutic platform. This review highlights the recent developments in polymer scaffolds for SCI engineering. Statement of Significance: How to improve the efficacy of neurological recovery after spinal cord injury (SCI) is always a challenge. Tissue engineering provides a promising strategy for SCI repair, and scaffolds are one of the most important elements in addition to cells and inducing factors. The review highlights recent development and future prospects in polymer scaffolds for SCI therapy. The review will guide future studies by outlining the requirements and characteristics of polymer scaffold technologies employed against SCI. Additionally, the peculiar properties of polymer materials used in the therapeutic process of SCI also have guiding significance to other tissue engineering approaches.